Responsive regulation and developing economics - John Braithwaite (University of Oxford, Global Economic Governance Programme (GEG), 2005)
Developing states with limited regulatory capacity might benefit from a responsive approach to regulation. Responsive regulation is a democratic ideal, incorporating notions of deliberative democracy and restorative justice. Responsive regulation conducted by regulatory networks of governmental and non-governmental actors allows for networking around capacity deficits. NGOs play a vital role in this kind of regulation. By utilizing NGOs and local social pressure, developing countries might develop a "regulatory society" model, bypassing the regulatory state. Where capacity remains limited, private bounty hunting (such as fees for successful private prosecutions) may become an appealing tool for achieving certain regulatory objectives.
Keywords: 330